Instructional challenges of incorporating aspects of critical literacy work in digitalised classrooms - Lisa Molin; Anna-Lena Godhe; Annika Lantz-Andersson (Cogent Education, 2018)
This study explores what opportunities for critical literacy work that can be distinguished in the practices of an emerging digitalised classroom and how teachers and students make use of these. Observations were conducted over the course of one semester in three subjects in a Swedish class of 13–14-year olds using individual tablets. The findings presented as thick descriptions suggest that different kinds of opportunities to develop critical literacy evolve in various activities and digital technologies become a resource in students’ work. However, these opportunities mainly occur in peer interactions outside the visible control of the teacher and never develop into further critical reflections. The study concludes that a deliberate emphasis on critical literacy work in the design of tasks, especially those that include digital technologies, creates opportunities for students to develop competences that support them in becoming confident users and producers of contemporary texts.